PENGARUH PENERAPAN DYNAMIC WORKING ARRANGEMENT DAN LINGKUNGAN KERJA NON FISIK TERHADAP KEPUASAN KERJA PADA PNS DI BPKAD PROVINSI JAWA BARAT - Agung Setiyawan; Mochamad Vrans Romi (ITB AAS Indonesia Surakarta, 2025)
Job satisfaction is one of the factors in obtaining and achieving maximum performance. When employee at all levels from lower level to upper feels satisfied, it positively impacts the development of the organization. BPKAD of West Java Province, there is indication of a high level of employee tardiness which may contribute to a decline in job satisfaction. Factors that can increase job satisfaction include the implementation of Dynamic Working Arrangement (DWA) and an ideal non-physical work environment. This study aims to examine the effect of the implementation of DWA and a non-physical work environment on the job satisfaction of civil servants in BPKAD of West Java Province, both partially and simultaneously. This research is quantitative research, the sample consists of 60 civil servants at BPKAD of West Java Province using the Slovin formula. The sampling technique applied was probability sampling, Data were collected through library research and field research. The data analysis methods used include descriptive and associative analysis, with multiple regression analysis conducted using SPSS version 24. The results show that the implementation of DWA and non-physical work environments, both partially and simultaneously, have an impact on the job satisfaction of civil servants at the BPKAD of West Java Province. It can be concluded that the increasing implementation of DWA and non-physical work environments.